Saran film production at Dow Chemical Company - Dow Chemical Company (1944)
General view of an unidentified female employee at work in the Dow Chemical Company's saran film manufacturing facilities in Midland, Michigan. The employee appears to be using a type of press to smooth lengths of saran film. Initially developed for the U.S. Army to wrap arms and equipment for transport during World War II, saran plastic was subsequently developed and marketed as Saran Wrap for household use.
Keywords: Plastics; Employees; Industries; Scientific apparatus and instruments; Dow Chemical Company; Plastics industry and trade; Women employees